Rancang Bangun Alat Penyiram Tanaman Otomatis Cabe Rawit Berbasis Mikrokontroller - Achmad Aminul Muklis; Ulul Ilmi (Universitas Islam Lamongan, 2020)
The development of today’s technology is increasing, people expect a tool that can help human work, for that technology becomes a necessity for humans. This undergraduate thesis makes a tool that can do the work of watering chili plants automatically. This tool aims to replace manual work to become automatic. The benefit obtained from this tool is to facilitate human work in watering chili plants. This tool uses soil sensors soil moisture that serves as a detector and sends commands to the ATmega328 microcontroller to turn on the driver relay so that the pump can flush the water as needed automatically. The making of this undergraduate thesis is done by designing, creating and implementing system components which include the ATmega328 Microcontroller as the controller, driver relay to turn on and turn off the water pump, the LCD (Cristal Display liquid) to display the score of soil moisture. The results of the research prove the tool made can work well and can be developed as expected. The tool can function when the soil moisture is above 1003 PH, however, it does not work if the soil moisture is less than 345PH.